2018
DOI: 10.1155/2018/7020538
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Angiomatoid Nodular Transformation: Laparoscopic Splenectomy as Therapeutic and Diagnostic Approach at the Same Time

Abstract: Introduction Sclerosing angiomatoid nodular transformation (SANT) of the spleen is a rare benign vascular lesion with unknown etiopathogenesis and with definite features of imaging, histopathology, and immunohistochemistry. It was first described by Martel et al. in 2004, and to date, only 151 cases have been reported. Case Description We report a case of SANT of the spleen detected in a 66-year-old Caucasian, without comorbidities, presented to our department with epigastric pain. We, also, presented a review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…Case reports published so far do not offer the possibility to distinguish a prominent clinical characteristic that can be associated with SANT. The most common symptoms that the patients experienced are a sense of abdominal discomfort and occasional dull abdominal pain [13]. Pain in the joints and laboratory analyses of our patient with high levels of C-reactive protein, fibrinogen, and leukocytes may indicate the existence of some type of general inflammatory response.…”
Section: Discussionmentioning
confidence: 67%
“…Case reports published so far do not offer the possibility to distinguish a prominent clinical characteristic that can be associated with SANT. The most common symptoms that the patients experienced are a sense of abdominal discomfort and occasional dull abdominal pain [13]. Pain in the joints and laboratory analyses of our patient with high levels of C-reactive protein, fibrinogen, and leukocytes may indicate the existence of some type of general inflammatory response.…”
Section: Discussionmentioning
confidence: 67%
“…Martel et al [1], in a series of 25 cases, have reported that SANT was significantly more common in women than in men, with an average age of 48.4 years. Recently, Cipolla et al [2], in a series of 152 cases, have reported that the ratio of occurrence of SANT in men and women was similar (1:1.08) and that the average age was 45.4 years. Although patients with SANT sometimes present with abdominal pain, most cases have no specific clinical symptoms and are often incidentally found during routine imaging.…”
Section: Discussionmentioning
confidence: 94%
“…They reported that SANT was significantly more common in women than in men, with an average age of 48.4 years. Recently, it has been reported that the ratio of occurrence of SANT in men and women was similar [2].…”
Section: Introductionmentioning
confidence: 99%
“…SANT of the spleen is a benign, nonhematolymphoid tumor that arises in the red pulp of the spleen (Tracher, Abbot). 8,9 Since its first description in 2004 by Martel et al ., 2 155 cases of SANT have been reported in adults (Cipolla, cao), 10,11 while only four cases have been reported in pediatric patients (Table 1). Zhang et al 6 described a 3-year-old child injured in a car accident with a postsplenectomy SANT diagnosis; Vyas et al 4 presented a case of SANT with inflammatory pseudotumor-like areas in an 11-year-old child with a history of trauma presenting with a rapidly growing splenic lesion; Agrawal et al 3 described SANT in a 12-year-old girl with upper quadrant discomfort which lasted six months; Kuybuli et al .…”
Section: Discussionmentioning
confidence: 99%